2022
DOI: 10.1186/s12859-022-05070-6
|View full text |Cite
|
Sign up to set email alerts
|

ENTAIL: yEt aNoTher amyloid fIbrils cLassifier

Abstract: Background This research aims to increase our knowledge of amyloidoses. These disorders cause incorrect protein folding, affecting protein functionality (on structure). Fibrillar deposits are the basis of some wellknown diseases, such as Alzheimer, Creutzfeldt–Jakob diseases and type II diabetes. For many of these amyloid proteins, the relative precursors are known. Discovering new protein precursors involved in forming amyloid fibril deposits would improve understanding the pathological proces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…With an accuracy on the test set of 81.80%, a sensibility of 100%, and a specificity of 63.63% on a balanced dataset, ENTAIL was based on the Naive Bayes Classifier with Unbounded Support and Gaussian Kernel Type. The investigation that was carried out showed that performance is superior in terms of performance on a balanced dataset [ 139 ] despite the various configurations of the tests.…”
Section: Computational Methods For Amyloid Fibril Identificationmentioning
confidence: 99%
“…With an accuracy on the test set of 81.80%, a sensibility of 100%, and a specificity of 63.63% on a balanced dataset, ENTAIL was based on the Naive Bayes Classifier with Unbounded Support and Gaussian Kernel Type. The investigation that was carried out showed that performance is superior in terms of performance on a balanced dataset [ 139 ] despite the various configurations of the tests.…”
Section: Computational Methods For Amyloid Fibril Identificationmentioning
confidence: 99%
“…Notably, the chosen datasets underscore the issue of class imbalance, where one dataset (CHSLB) exhibits balanced classes (51% and 49%), while six out of eight datasets have one class representing over 60% of the samples. In the Kidney-Abu Dhabi dataset, one class comprises a striking 89% of the data, highlighting the significance of addressing this common challenge for accurate predictions in medical contexts [83], [84]. In addressing the inherent imbalance within the datasets, the proposed methodology incorporated a combination of strategic adjustments within the XGBoost framework.…”
Section: Resultsmentioning
confidence: 99%
“…[9]. When it comes to the performance of these algorithms, the use of a balanced medical dataset results in good performance [10], [11].…”
Section: Related Workmentioning
confidence: 99%